Solitary fibrous tumor (SFT) of paratesticular origin; sonographic and histological pictures - Mohsin Sheraz Mughal; Hasan M. Mirza; Syed Hussain Abbas; Ikwinder P. Kaur; Abdalrahman Almeligy; Wael Ghali (Elsevier, 2020)
Solitary fibrous tumors (SFTs) are fibroblastic mesenchymal tumors, commonly benign but rarely can be malignant. We present a 36 years old male who had a painless right testicular mass, slowly growing over four years. On physical examination, he had a firm, warm right testicular mass of 11x9x5 cm. There was no inguinal lymphadenopathy or gynecomastia. Testicular ultrasound showed a large extratesticular, heterogeneous, and hypoechoic mass anterolateral to the right testicle with increased internal vascularity. Serum level for Alpha-fetoprotein (AFP), beta HCG were within normal limits. A contrast-enhanced CT scan of the abdomen, pelvis, and chest was negative for a metastatic disease process. The patient underwent right radical orchiectomy. Tumor cells were diffusely reactive with CD-34, STAT-6, and negative for calretinin, desmin, smooth muscle actin, cytokeratin, epithelial membrane antigen, and S-100, supporting the diagnosis of SFT of paratesticular origin. SFTs are usually benign but a study suggested that 10-15% SFTs can be malignant. So, a regular follow up and documenting the non-malignant nature of the disease is necessary.